Model-based analysis of sustainable energy transition: A case study of Portugal's regional wind and solar power generation - Oliveira, A.; Doménech Martínez, S.; Collado, J. V.; Meireles, M.; López-Maciel, M.; Lima, F.; Ramalho, E.; Robaina, M.; Madaleno, M.; Dias, M. F. (2024 20th International Conference on the European Energy Market (EEM), 2024)
In the context of the R3EA project, funded by the Portuguese Foundation for Science and Technology (FCT), we analyse a set of selected future power system scenarios to assess the impact, on the Iberian electricity market (MIBEL), of installing wind and solar generation capacity in Portugal's Centro Region. We use the long-term MIBEL operation and planning model CEVESA. The scenarios are designed based on the current economic situation and the last National Energy and Climate Plan drafts for Portugal and Spain, by distributing the expected new wind and solar generation capacity differently among Portugal regions, also considering the flexible demand for producing electrolytic hydrogen. Market prices, capture prices and production per technology are analysed to assess this impact. Results show that regional investments have no significant impact on the MIBEL variables analysed.